Nursing actions for prevention and treatment of complications in intestinal stomies (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: To identify in the literature the main nursing actions for prevention and treatment of the most frequent complications in intestinal elimination stomies. Methods: Integrative review that followed the phases: identifi cation of the theme and selection of the research question; establishment of criteria for inclusion and exclusion of studies; categorization of studies; evaluation of studies included in the integrative review; interpretation of results; and synthesis of knowledge. The period used was from January 2007 to June 2017, in the databases and in the portals Medical Literature Analysis and Retrieval System Online (MEDLINE), Biblioteca Virtual em Saúde (BVS), Excerpta Medica database (Embase), Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Scopus Info Site. The descriptors used were ostomy, nursing and postoperative complications. Results: Eleven articles answered the guiding question: which nursing actions can be used to prevent and treat complications in intestinal ostomies? The most commonly reported complications were a parastomal hernia, stenosis, retraction of the ostomy and mucocutaneous separation. The most cited nursing actions were preoperative demarcation and follow-up with specialist nurses in the pre- and postoperative periods. Conclusion: The role of the stomatherapist nurse is essential for the prevention and treatment of complications in the intestinal ostomies, but more studies of high impact are necessary to guide their actions.
Keywords: Ostomy; Nursing; Postoperative Complications; Estomatherapy.